HUBUNGAN ANTARA SELBSVERTRAUEN DAN SPRECHFERTIGKEIT BAHASA JERMAN SISWA KELAS XI SMA NEGERI 8 MAKASSAR - Nurlina, Nurlina; R., Mantasiah; Azizah, Laelah (Universitas Negeri Makassar, 2020)
Abstract. This research was conducted to obtain data and information about the relationship between Selbsvertrauen and Sprechfertigkeit German Language Class XI students of SMA Negeri 8 Makassar. The variable in this study is Selbsvertrauen and the dependent variable is Sprechfertikgeit. The population in this study were all class XI of SMA Negeri 8 Makassar consisting of 3 classes, the sample in this study were students of class XI MIPA 2 at SMA Negeri 8 Makassar with a total of 35 people. The results of this study obtained the results of speaking skills and questionnaire tests. Based on the results of the study indicate that the R count is greater than the R table (0.796 <0.334). The analysis showed that there was a relation between Selbsvertrauen and Sprechfertigkeit German Language Class XI students at SMA Negeri 8 Makassar.